Evaluation of the efficacy of transcorneal electric stimulation therapy in retinitis pigmentosa patients with electrophysiological and structural tests - Hamurcu, Mualla Sahin; Aydogmuş, Sema Akkan; SARICAOĞLU, M. Sinan (International Journal of Clinical and Experimental Ophthalmology, 2020)
A Statement of significance: This study shows that the effect of transcorneal electrical stimulation (TES) therapy as a stimulator device in retinitis pigmentosa (RP)patients with have a significant increase in visual acuity and shortening of p100 latency in pattern visual evoked potential (pVEP) test during 3 months follow up. Purpose: To assess the safety and efficacy of TES therapy with electrophysiological and structural tests in RP patients. Methods: Thirty four eyes of 17 RP patients were included in the study. Initial examination included best corrected visual acuity (BCVA) and visual field (VF) test (Humphrey). Central macular thickness (CMT), retinal nerve fiber layer thickness (RNFLT) and choroidal thickness (CT) were measured with using swept-source optical coherence tomography (OCT). The patients were tested by Metrovision brand monpack model visual eletrophysiology device for pVEP and flash electroretinogram (fERG) tests. Patients were seen 12 times during 3 months: initial visit for screening and weekly visits for TES. All tests were repeated 3 times. The results of pre and post TES therapy were compared. Results: Patients’ baseline BCVA was 0,34 ± 0,22. The increase in the last visit BCVA was significant (p : .001) and it was 0.50 ± 0.29. The difference between CMT, RNLF and CT pre and post TES therapy were not significant (p > .05). The mean latencies of the 120’ pattern p100 waves that patients could see were shortened and statistically significant (p = .04). The peaks amplitudes of the 120’ pattern p100 waves that patients could see were increased; but not statistically significant (p :. 19). Conclusion: This study shows that the safety of TES as a stimulator device in our patient group and the effect on this group have a significant increase in visual acuity and shortening of p100 latency in pVEP test during 3 months follow up.